Pain and Inflammation Management in Older Adults: A Brazilian Consensus of Potentially Inappropriate Medication and Their Alternative Therapies - Motter, Fabiane Raquel; Hilmer, Sarah Nicole; Paniz, Vera Maria Vieira (Frontiers in Pharmacology, 2019)
Purpose: The aim of the present study was to develop and validate a Potentially Inappropriate Medications (PIM) list and alternative therapies for treatment of pain and inflammation in older people adapted to the Brazilian context. Methods: A preliminary PIM list suitable for the Brazilian market was developed on the basis of three published international PIM lists (Beers 2015, Screening Tool of Older People's Potentially Inappropriate Prescriptions - 2005, European Union (7) PIM list). We used the modified Delphi technique (two-round) to validate concerns of use and alternative therapies related to PIM for treatment of pain and inflammation in older adults ≥65 years in Brazil. The panel involved nine Brazilian experts in geriatric pharmacotherapy. All items with mean Likert scale score ≥4.0 (agree) and the lower limit of 95% confidence interval ≥4.0 were considered validated in this study. Results: At the end of the consensus process, 94 (65.3%) items of 144 were validated. In total, consensus was reached for 33/35 (94.3%) concerns about drugs that should be avoided in older patients regardless of diagnosis, for 22/23 (95.7%) concerns about drugs that should be avoided in older patients with specific conditions or diseases, for 11/23 (47.8%) with special considerations of use, and for 28/63 (44.4%) of therapeutic alternatives. Conclusion: Although these criteria are not designed to replace clinical judgement, PIM and alternative therapies lists can be useful to inform prescribers, pharmacists, and health care planners and may serve as a starting point for safe and effective use of medications in older people.